The reduction of dietary sucrose improves dyslipidemia, adiposity, and insulin secretion in an insulin-resistant rat model - Fortino, María Alejandra (2007)
The purpose of the present work was to investigate whether changes in the type of carbohydrate in the diet are able to improve and/or reverse hyperlipemia, impaired glucose homeostasis, and insulin secretion from beta cells induced in rats by chronically feeding a high sucrose intake.Methods For 30 wk male Wistar rats received a sucrose-rich diet (63% w/w) or a control diet in which sucrose was replaced by starch. After this period, the sucrose-fed animals were randomly divided into two groups: the first group continued with this diet up to 42 wk and the other received the same diet but with a 20% reduction in the amount of sucrose and the rest of the carbohydrate being replaced by starch. Rats were fed with this diet for the next 12 wk.The reduction of the amount of sucrose in the diet showed a substantial improvement of dyslipidemia associated with an amelioration of ?in vivo? very low-density lipoprotein-triacylglycerol secretion and triacylglycerol removal rate from the circulation. Glucose homeostasis and glucose-induced insulin release from beta cells were improved although these values did not reach those observed in rats fed a control diet. Visceral adiposity was also significantly reduced. Conclusion: These data are consistent with the suggestion that the composition of the diet could contribute to improvements in dyslipidemia, insulin resistance, and adiposity by direct effects on the lipid metabolism and insulin action and indirectly through the reduction of visceral fat mass and distribution.